1995
DOI: 10.1111/j.1365-2796.1995.tb01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term anticoagulant therapy in cerebrovascular disease: does bleeding outweigh the benefit?

Abstract: The total results suggest a positive net effect of ACT in patients with NVAF and TIAs. Without comparable data, no definite conclusions concerning the effect of ACT on patients with SIP can be drawn. The rate of bleeding complications was similar to that in other studied materials and is not negligible. In patients with SIP and TIAs, ACT beyond 6 months should probably only be continued if aspirin is not tolerated or has proven ineffective in the particular patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The reported mean incidence of major bleeding in the anticoagulated population is estimated to be 2.4% to 4.6% per year, and fatal hemorrhage incidence is 0.1% to 1.6% per year [22,[25][26][27][28][29].…”
Section: Anticoagulant Bleedingmentioning
confidence: 99%
“…The reported mean incidence of major bleeding in the anticoagulated population is estimated to be 2.4% to 4.6% per year, and fatal hemorrhage incidence is 0.1% to 1.6% per year [22,[25][26][27][28][29].…”
Section: Anticoagulant Bleedingmentioning
confidence: 99%
“…Therefore, SDH and intracerebral hemorrhage fatality rates when receiving no therapy 15,[23][24][25][26][27][28][29][30][31][32] and warfarin 15,17,19,23,24,[26][27][28][32][33][34][35][36][37][38][39][40] were estimated by pooling studies that reported consecutive cases. For persons receiving aspirin at the time of their SDH or intracerebral hemorrhage, information about their outcomes was not available.…”
Section: Discussionmentioning
confidence: 99%
“…Estimations of its frequency range from 0.3 to 4.6% per year (1,2). The absolute rate of ICH in patients older than age 60 years who are treated with conventional intensities of anticoagulation ranges from 0.3 to 1% per year, and 60% of cases are fatal (3).…”
Section: Introductionmentioning
confidence: 99%